ANALYSIS OF PROPERTIES OF CONCRETE USING STEEL FIBERS AS FIBER REINFORCEMENT ADMIXTURE - Gadgihalli, Vishal; Meena; Sindu; Dinakar, Raghavendra Prasad (International Journal of Research -GRANTHAALAYAH, 2017)
Fiber reinforced concrete is composite material consisting of mixtures of cement, mortar or concrete, discontinuous discrete uniform dispersed suitable fibers. Fiber reinforced concrete are of different types and properties. In this paper analysis of properties of concrete using steel fibre as fiber reinforcement admixture is studied and verified the strength of concrete to normal plane concrete with absence of admixtures. Using steel fibers as fiber reinforcement admixture increases bond strength by enhancing surface tension as steel is better in taking flexural strength this gives better results, hence we can use this steel fiber reinforcement to concrete where the compressive and flexural strength place a crucial role in construction and maintenance.